Nasikh dan Mansukh dengan berbagai Permasalahannya dalam Studi Al-Qur’an - Happyana, Luat (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
This article tries to examine the theme of Nasikh and Mansukh with various problems in the study of the Koran. The approach taken in this discussion is a qualitative approach using literature study. The conclusion from this research on Nasikh and Mansukh is that Nasikh can be interpreted as remover, substitute, changer or transferr. Meanwhile, mansukh is defined as something that is removed, replaced, changed or moved. The Nasikh component consists of a statement indicating that the existing law has been canceled, there must be a Naskh, there must be a Mansukh and there must be someone who is legally burdened with it. In the Naskh, conditions are required, namely that the law that was Mansukh is Sharia law, the argument for the abolition of this law is the Sharia book which came later from the book that was Mansukh, and the law of the book that is deleted or removed is not bound or limited by a certain time. Key words: nasikh, mansukh, ulumul qur'an